The potential of 4D sonography in the assessment of fetal neurobehavior - multicentric study in high-risk pregnancies - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2010)
Objective: An evolving challenge for obstetrician is to better define normal and abnormal fetal neurological function in utero in order to better predict antenatally which fetuses are at risk for adverse neurological outcome. Patients and methods: Prenatal neurological assessment in high-risk fetuses using four-dimensional ultrasound applying the recently developed Kurjak antenatal neurodevelopmental test (KANET). Postnatal neurological assessment was performed using Amiel Tison's neurological assessment at term (ATNAT) for all live-borns and general movement (GM) assessment for those with borderline and abnormal ATNAT. Results: Inclusion criteria were met by 288 pregnant women in four centers of whom 266 gave birth to a live-born baby. It was revealed that 234 fetuses were neurologically normal, 7 abnormal and 25 borderline. Out of 7 abnormal fetuses ATNAT was borderline in 5 and abnormal in 2, whereas GM assessment was abnormal in 5 and definitely abnormal in 2. Out of 25 KANET borderline fetuses, ATNAT was normal in 7, borderline in 17 and abnormal in 1, whereas the GM assessment was as follows: normal optimal in 4, normal suboptimal in 20, and abnormal in 1. In summary, out of 32 borderline and abnormal fetuses ATNAT was normal in 7, borderline in 22 and abnormal in 3; GM assessment was normal optimal in 4, normal suboptimal in 20, abnormal in 6 and definitely abnormal in 2. Conclusion: The sonographic test requires further studies before being recommended for wider clinical practice.
Keywords: Fetal behavior; neurological risk; prenatal neurological test; 4D ultrasound (4D US); CEREBRAL-PALSY; 4-DIMENSIONAL SONOGRAPHY; GENERAL MOVEMENTS; NORMAL STANDARDS; BEHAVIOR; WOMEN; STATE; ULTRASOUND; DISORDERS; MOTILITY